Strain hardening at elevated temperatures induced by dynamic crystallization of an Al88Ni4Y8 amorphous alloy - Yang, H. W. (2013)
Tensile tests were carried out on amorphous Al88Ni4Y8 ribbons at room and high temperatures. The fracture strength at room temperature was 889 MPa, with an elastic strain of ∼1.35%. At 200 °C the tensile strength was 816 MPa, with a total strain of 16.8%. Modulated differential scanning calorimeter results revealed the existence of a “hidden” glass transition, which resulted in viscous flow and large plastic deformation. Dynamic crystallization during tensile tests accounted for the observed strain hardening behavior.